Evaluation of the utility of unidirectional Doppler: effect in the study of arteriopathies of the leg - Castro, Danilo; Balboa, Oscar; Matteucci, Pablo; Tchekmedyian, Vartan (Cirugía del Uruguay, 1984)
Analysis of 85 patients with symptoms of peripheric arterial insufficiency by comparison of the Doppler hemo. dynamic study and arteriography. To this end, each limb is divided into three segments: the aortoiliac, the femoropopliteal and the distal popliteal segments. In the 320 segments studied by Doppler a 92% of sensibility, a 97% of specificity and a high reliabilily coefficient in the diagnosis were found, revealed by a 0,89 rate of Youdan index, which turns Doppler into a first class method for the study of pa• lients with peripheric vascular problems. Presentado